Evaluasi Program Kegiatan Ibadah Bersama di SD Inpres Oesapa Menggunakan Model Cipp - Meti Maria Enjela Neolaka; Onci Amida Nope; Yulita Laosana; Oktavia Delvana Tilman; Yonathan Foeh (Master Manajemen, 2025)
Instilling religious values from an early age is a crucial component in shaping students' character, particularly through religious education at the elementary school level. SD Inpres Oesapa routinely implements a joint worship program as a form of integrating spiritual values into formal education. This study aims to evaluate the implementation of the joint worship program at SD Inpres Oesapa using the CIPP evaluation model (Context, Input, Process, Product), to assess the program's effectiveness and provide recommendations for improvement. The study employs a qualitative approach with in-depth interviews, observation, and documentation techniques. The contextual evaluation shows that the program aligns with the school’s vision and receives strong support from teachers, parents, and the surrounding community. In terms of input, the program is supported by religious education teachers and necessary facilities, although there is still a need to improve teaching competence. The process evaluation reveals that the worship activities, held twice a month, are well-received by students, who feel enthusiastic and spiritually engaged. Product evaluation indicates positive behavioral changes in students, such as increased discipline, responsibility, and religious habits, though challenges remain for younger students with lower attention spans. Overall, the joint worship program has proven effective in fostering students' religious character and is recommended for further development with contextual approaches suitable to different grade levels.